INOVASI PELAYANAN PUBLIK BERBASIS E-GOVERNMENT PADA APLIKASI LIBAS DI KOTA SEMARANG - Allicia Steffi Maharani; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study is motivated by the demand for digital-based public service transformation at the local government level, particularly in Kota Semarang. The existing problems include limitations in the reporting system, slow response times, and ineffective service delivery. Polrestabes Semarang introduced the LIBAS Application as an e-government innovation to enhance convenience, speed, transparency, and accountability in public services. This research aims to analyze the improvement of accountability through the application using a descriptive qualitative method. The study applies public service theory using public service indicators. Data collection techniques include interviews, observation, and literature review. The results show that since its launch in 2021, the LIBAS Application has significantly supported digital police reporting services. Based on public service indicators, the tangible and empathy aspects are more prominent as they are directly perceived by the community. However, the reliability indicator remains a weakness due to the lack of consistent service assurance. In addition, the socialization of the application has not been optimal, as some residents are still unaware of its existence. Overall, the implementation of the LIBAS Application demonstrates positive achievements in improving accessibility and the speed of digital services. This innovation is considered fairly effective, efficient, and accountable, although it still faces challenges such as limited digital literacy and the need for policy and procedural updates.